ONLINE ADOLESCENT'S SELF-DISCLOSURE AS SOCIAL MEDIA USERS: THE ROLE OF EXTRAVERSION PERSONALITY, PERCEPTION OF PRIVACY RISK, CONVENIENCE OF RELATIONSHIP MAINTENANCE, AND SELF-PRESENTATION - Rahardjo, Wahyu; Qomariyah, Nurul; Hermita, Matrissya; Suhatril, Ruddy J.; Marwan, Mochammad Akbar; Andriani, Inge (Jurnal Psikologi, 2020)
Adolescences' excessive online self-disclosure is now a social phenomenon arising in social media use. The adolescences also tend to share their privacy. This study aims to determine whether extraversion personality, perceived privacy risks, the convenience of maintaining relationships, and online self-presentation influence self-disclosure in adolescents. This study involved 619 adolescents (185 male and 434 female) aged 13-22 years (M = 19.39, SD = 1.83). The participants are active social media users collected from several areas in Indonesia. Multiple regression analysis is used to test the hypothesis. The results show that several variables simultaneously affect online self-disclosure in adolescents (R2 = .422; F (4, 614) = 111.944, p < .01). However, in details, online self-presentation does not have a significant effect on online self-disclosure among adolescents. This result shows that personality factors and adolescent perceptions of the low privacy risk on social media, as well as the goal of maintaining social relations with other members of social media, encourage them to be more online disclose on social media.